1981
DOI: 10.2190/t9gt-qjcu-adjp-37er
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Search for Stages of Widowhood

Abstract: Developmental theory and clinical experience suggest that stages of adjustment to widowhood beyond the initial stages of grief may exist. Structured interviews with 193 widowed community residents over sixty-two were conducted as part of a needs assessment survey of the elderly in Wichita. One hundred fifty-one variables including eight psycho-social needs, the Philadelphia Geriatric Center Morale scale, age perception, future orientation, presence of or desire for a confidant, contact with children, and parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Regarding descriptive statistics, the mean GHQ and SRQ‐D scores showed that many of the bereaved remained in poor health, especially in terms of mental health, despite the fact that most of them had been bereaved for >5 years. This result is consistent with the evidence that the impact of bereavement persists for several years 3,25,29,35–37 . The mean scores on these scales exceeded the clinical thresholds, except for those bereaved due to chronic illness.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding descriptive statistics, the mean GHQ and SRQ‐D scores showed that many of the bereaved remained in poor health, especially in terms of mental health, despite the fact that most of them had been bereaved for >5 years. This result is consistent with the evidence that the impact of bereavement persists for several years 3,25,29,35–37 . The mean scores on these scales exceeded the clinical thresholds, except for those bereaved due to chronic illness.…”
Section: Discussionsupporting
confidence: 90%
“…The study of Johnson (2002) similarly found bereaved elders to be at moderate nutritional risk compared to married controls, and Schone & Weinick (1998) found an effect of bereavement status on skipping breakfast, but among women only. Compared to longer-term widow(er)s, Barrett & Schneweis (1980) found that recently bereaved elders needed help finding information on food preparation and did not believe they ate nutritious meals. Qualitative analyses identified significant themes surrounding 1) skills related to shopping and preparing food, 2) the social significant of eating, and 3) general nutritional quality (Wylie et al, 1999; Johnson, 2002).…”
Section: Resultsmentioning
confidence: 97%
“…Canadian and American writers are concerned that widowed women are stereotyped as little more than women who have lost their spouses (Gee & Kimball, 1987;Silverman, 1986), and that widowhood has been constructed within the context of crisis and personal affliction (Barrett & Schneweis, 1980;Wenz, 1977), as a gateway to profound bereavement and long-term mental health problems (Kirshling & Barron McBride, 1989;Lund, 1989;Prigerson, Frank & Kasl, 1995;Stein & Susser, 1969). Other studies associate widowhood with premature mortality (Bowling, 1988;Mendes de Leon, Kasl & Jacobs, 1994) and suicide (Guohua, 1995).…”
Section: Literature Reviewmentioning
confidence: 99%